Morphological changes in nanoparticulate silver films due to electron beam irradiation of polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions With Materials and Atoms, 2011)
Results of the studies on the effect of 8 MeV electron beam irradiation of polystyrene substrates on the morphology of silver particulate films deposited at 455 K in a vacuum of 8 x 10(-6) Torr are reported. Optical absorption studies show the presence of transverse and longitudinal plasmon resonance for films deposited on irradiated polystyrene. Scanning electron microscopy reveals a decrease in particle size with smaller inter-particle separation for irradiated films. Larger clusters are formed in the case of films deposited on polystyrene after 300 h of irradiation. In this paper, we show that the morphology of silver nanoparticulate films can be modified by electron irradiation of inert polymer substrates like polystyrene. The change observed due to irradiation is attributed to the formation of free radicals, thereby altering the polymer-metal interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electron bombardment; Optical properties; Particulate films; Polymers; Silver; surface morphology